Demographic predictors of students’ science participation over the age of 16: an Australian case study - Cooper, Grant; Berry, Amanda; Baglin, James (SPRINGER, 2020)
Using the Longitudinal Surveys of Australian Youth (LSAY) data, this paper aimed to examine if, and to what extent, demographic factors predict students’ participation in science over the age of 16 (post-16). While all the students participating in this study are attending Australian schools, the comprehensiveness of these datasets, together with inclusion of studies from around the world provides a useful reference point for an international audience. Over 7000 students are included in the analysis of this paper. Characteristics of focus in this paper include groups who have been identified as being underrepresented in past studies including Indigenous students, those from lower-socio-economic status (SES) backgrounds, sex differences and immigrants. Among the factors tested, Indigenous status was the strongest negative predictor of post-16 science participation. SES was also a relatively strong predictor of post-16 science participation. Compared to students categorised with an Australian-ancestry, first-generation and foreign-background students were more likely to participate in post-16 science. The findings of this study contribute to existing research on debates about equity and trends in science participation.